Step
*
1
1
of Lemma
qmul_preserves_qless
1. a : ℚ
2. b : ℚ
3. c : ℚ
4. 0 < c
5. a < b
⊢ 0 < -(a * c) + (b * c)
BY
{ xxx(Subst ⌜(-(a * c) + (b * c)) = ((b - a) * c) ∈ ℚ⌝ 0⋅ THENA Auto)xxx }
1
1. a : ℚ
2. b : ℚ
3. c : ℚ
4. 0 < c
5. a < b
⊢ 0 < (b - a) * c
Latex:
Latex:
1.  a  :  \mBbbQ{}
2.  b  :  \mBbbQ{}
3.  c  :  \mBbbQ{}
4.  0  <  c
5.  a  <  b
\mvdash{}  0  <  -(a  *  c)  +  (b  *  c)
By
Latex:
xxx(Subst  \mkleeneopen{}(-(a  *  c)  +  (b  *  c))  =  ((b  -  a)  *  c)\mkleeneclose{}  0\mcdot{}  THENA  Auto)xxx
Home
Index